Thermotolerance screening of Brassica carinata genotypes using in vitro seed germination assay - Leelawattie Persaud; Naflath Thenveettil; Ramdeo Seepaul; Bisoondat Macoon; Krishna N. Reddy; Kambham Raja Reddy (Heliyon)
Temperature is a fundamental factor influencing the processes of seed germination. Investigating the response of carinata to thermal stress and establishing a dependable and efficient method for screening thermotolerance will enhance breeding programs and model applications. We assessed the response of 12 carinata genotypes to a range of eight temperatures, spanning from 8 to 37 °C, throughout the germination process. A four-parameter Weibull function effectively characterized the seed germination time course across various temperatures and genotypes. Quadratic functions effectively characterize the maximum seed germination and the rate of seed germination as a function of temperature across various genotypes. The average cardinal temperatures recorded were −0.14, 20.41, and 40.70 °C for maximum seed germination, while the temperatures for seed germination rate were 5.30 °C, 24.51 °C, and 43.71 °C, corresponding to minimum, optimum, and maximum conditions, respectively. A notable variation was observed in maximum seed germination, seed germination rate, and cardinal temperatures across different genotypes. The specified parameters were employed to screen the genotypes for their thermotolerance capabilities. The analysis of principal components and the cumulative response indices effectively characterized carinata genotypes for high- and low-temperature tolerance exhibiting distinct characteristics. The AX17004 was identified as a genotype with significant tolerance to high temperatures, whereas AX17009 demonstrated remarkable tolerance to low temperatures. In contrast, AX17002 exhibited sensitivity to both high and low-temperature stress. According to the classification of breed types, both double haploid and hybrid groups revealed consistent thermotolerance responses during the germination phase. In contrast, the inbred group exhibited a wider response cluster to both minimum and maximum temperatures. The in vitro assay method presents a cost-effective approach for evaluating thermotolerance in carinata genotypes.